The management of patients with osteoarthritis by a primary care physician: focus on efficacy and safety - M. S. Svetlova (Медицинский совет, 2018)
The management of patients with osteoarthritis and comorbidity in the general medical practice is an urgent task. The article presents the recommendations of recent years on this problem, both international and national ones. The basic therapy for comorbid patients with osteoarthritis includes slow-acting anti-arthrosis drugs, mainly chondroitin sulfate and glucosamine, as well as their combination. The efficacy and safety of the combination has been proved by studies in recent years. The article presents an algorithm for managing comorbid patients with osteoarthritis by a primary care physician, taking into account concomitant diseases.